L1.1 Is Involved in Spinal Cord Regeneration in Adult Zebrafish - Becker, Catherina G. (J Neurosci, 2004)
Adult zebrafish, in contrast to mammals, regrow axons descending from the brainstem after spinal cord transection. L1.1, a homolog of the mammalian recognition molecule L1, is upregulated by brainstem neurons during axon regrowth. However, its functional relevance for regeneration is unclear. Here, we show with a novel morpholino-based approach that reducing L1.1 protein expression leads to impaired locomotor recovery as well as reduced regrowth and synapse formation of axons of supraspinal origin after spinal cord transection. This indicates that L1.1 contributes to successful regrowth of axons from the brainstem and locomotor recovery after spinal cord transection in adult zebrafish.